ANALISIS AKURASI ARAH KIBLAT MASJID NASRULLAH DUSUN SALEMBA DESA TIMBUSENG KABUPATEN GOWA MENGGUNAKAN METODE ISTIWA ‘AINI: Indonesia - Alamsyah alam (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2026)
This study aims to analyze the accuracy of the qibla direction of Nasrullah Mosque, located in Palemba Hamlet, Timbuseng Village, Gowa Regency, using the Istiwa Aini method. This mosque is one of the oldest mosques in Timbuseng Village and was previously known as Al-Muhajirin Mosque before being renamed Nasrullah Mosque. This research employs a descriptive field-based approach within the framework of Islamic astronomy (ilmu falak). Data were obtained through direct observation of the mihrab orientation, prayer rows, and mosque building structure, and were then verified using applications and Istiwa Aini instruments. The calculation results show that the qibla azimuth is 292°28’05.90”, with field measurements conducted using the sun’s shadow as the basis for drawing the qibla direction line. The findings indicate that the qibla direction of Nasrullah Mosque is highly accurate because the measured line corresponds with the mosque’s qibla orientation. These findings reinforce the importance of scientifically verifying the qibla direction of old mosques in order to provide certainty in worship for the community.